Frankfurt a.M.-Bockenheim - Die wirtschafts- und sozialräumliche Problematik eines innenstadtnahen Altbau- und Sanierungsgebietes - Vorlaufer, Karl (ERDKUNDE, 1982)
Bockenheim is an urban quarter of Frankfurt, which developed from a farming village to an important location for manufacturing industry and working class housing. It manifests the problems inherited from early industrialization and urbanisation by a district close to the inner city. Most of the old stock of building is characterised by the strongly marked mixed functions of manufacturing and residence, by closely packed buildings together with narrow, intricate backyards. At least in parts the design and equipment of the housing units show considerable defects; the mixed function and the closeness of buildings result in serious ecological burdens on the residential environment and a below-average availability of private and public open-spaces. Bockenheim also demonstrates the socioeconomic structural characteristics typical of such quarters. The residential population is decreasing fast; it has a growing, and by comparison with Frankfurt, an overall disproportionately high number of foreigners, a high degree of mobility, as well as a high number of single-person households. During recent years numerous firms, especially those of the manufacturing industry, relocated their premises on the periphery of the agglomeration in order to overcome the spatial restrictions encountered in Bockenheim; the importance of Bockenheim as a place of work is diminishing. In large parts of the quarter urban renewal is becoming necessary; this has been prepared by the city administration on the basis of the law for the promotion of urban renewal since 1972, and has been carried out since 1978 in two clearly defined areas; it is due to be completed by 1990.